Development of "LELI" Application to Enhance Mathematics Critical Thinking of Quality Generations in Society 5.0 Era - Rosyadi, Alfiani Athma Putri; Aulia Firdaus Azzahra; Meisya Andjani Nagaya Dara; Vina Ananda Aprilia (Kreano, Jurnal Matematika Kreatif-Inovatif, 2025)
Students' mathematical critical thinking skills are one of the important competencies that need to be developed to face the challenges of the Society 5.0 era. However, conventional learning, which is less interactive, is often an obstacle to improving these abilities. This study aims to develop an interactive learning application called "LELI" to enhance junior high school students' mathematical critical thinking skills in the context of integer material. This type of research is a development approach utilizing the Research and Development (R&D) method in conjunction with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The subjects of this study were grade VII junior high school students in the Merdeka Curriculum. Data collection techniques included observation, unstructured interviews, and tests. Data collection instruments used expert validation sheets, student response questionnaire sheets, and pre-tests and post-tests. The results showed that the "LELI" application was valid (77%), very practical (95.95%), and effective in improving critical thinking skills, with the average student score increasing from 65% (good) to 85% (very good). Based on the results obtained, the "LELI" application is valid, practical, and effective in improving the critical thinking skills of junior high school students in learning mathematics on integer material. These findings suggest that the "LELI" application can be a strategic solution for educators to enhance critical mathematical thinking skills in alignment with the demands of the Society 5.0 era. Abstrak Kemampuan berpikir kritis matematis siswa menjadi salah satu kompetensi penting yang perlu dikembangkan untuk menghadapi tantangan era Society 5.0. Namun, pembelajaran konvensional yang kurang interaktif seringkali menjadi kendala dalam meningkatkan kemampuan tersebut. Penelitian ini bertujuan untuk mengembangkan aplikasi pembelajaran interaktif bernama "LELI" untuk meningkatkan kemampuan berpikir kritis matematis siswa SMP pada materi bilangan bulat. Jenis penelitian ini adalah pengembangan menggunakan metode Research and Development (R&D) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Subjek penelitian ini adalah siswa kelas VII SMP pada kurikulum merdeka. Teknik pengumpulan data berupa observasi, wawancara secara tidak terstruktur, dan tes. Instrumen pengumpulan data menggunakan lembar validasi ahli, lembar angket respon siswa, serta pre-test dan post-test. Hasil menunjukkan aplikasi "LELI" valid (77%), sangat praktis (95,95%), dan efektif meningkatkan kemampuan berpikir kritis, dengan score rata-rata siswa meningkat dari 65% (baik) menjadi 85% (sangat baik). Berdasarkan hasil yang diperoleh, maka aplikasi "LELI" valid, praktis, dan efektif untuk meningkatkan kemampuan berpikir kritis siswa SMP pada pembelajaran matematika materi bilangan bulat. Temuan ini menunjukkan bahwa aplikasi “LELI” dapat menjadi solusi strategis bagi para pendidik untuk meningkatkan kemampuan berpikir kritis matematis yang sejalan dengan tuntutan era society 5.0.